Synthesis and Structural Analysis of Iron Doped Zinc Oxide Nanoparticles - Chauhan, Ruby; Kumar, Ashavani; Pal Chaudhary, Ram (Asian Journal of Chemistry, 2011)
Nanocrystals of undoped and iron doped zinc oxide (Zn1-xFexO, where x = 0.00 to 0.05) were synthesized by coprecipitation method. Crystalline phases and optical absorption of prepared samples were determined by X-ray diffraction and UV-visible spectrophotometer. The average particles size was determined from X-ray line broadening. X-ray analyses revealed the formation of the hexagonal wurtzite ZnO with secondary phase in the Fe-doped sample. The incorporation of iron in place of zinc provoked an increase in the size of nanocrystals as compared to undoped ZnO. Crystalline size of nanocrystals varied from 27 to 41 nm as the calcinations temperature increased. Optical absorption measurement indicated red shift in the absorption band edge upon Fe doping. The band gap value was found to decrease from 2.90 to 2.85 eV with iron (5 %) doping at 800 ºC.